Physical activity patterns in type 1 diabetes in Spain: The SED1 study - F Gómez-Peralta; E Menéndez; S Conde; I Conget; A Novials; on behalf of SED and SED1 study investigators (BMC, 2023)
Abstract Aims To describe the physical activity (PA) frequency and intensity in the Spanish type 1 diabetes mellitus (T1D) population and its association with their glycemic control. Methods A cross-sectional observational study was carried out in 75 Spanish public hospitals (the SED1 study). T1D patients over 14years of age self-completed the International Physical Activity Questionnaire (IPAQ) to determine their level of exercise. The relationship between PA frequency and intensity in T1D patients and glycemic control and the diabetes therapeutic education received were analyzed. Results A total of 592 patients were evaluable. A 6.8% of the sample performed light PA, 20.9% moderate and 72.3% vigorous. Estimated PA presented a high inter-individual variability. Men consumed more energy (METS) than women, these differences being more noticeable in vigorous METS (2865.80 in men vs 1352.12 in women). Women invested more min/week in the domestic and garden area (639.03 vs 344.39, p = 0,022). A correlation between glycemic control and the METs was not observed. Conclusions The Spanish T1D population performed PA in a higher frequency and intensity than the general population. A relationship between PA and glycemic control couldn´t be shown. However, limitations of the study should be kept in mind to discard a long-term positive influence.